Socio-economic Challenges Faced by Newly Resettled Families (NRF): A Case Study of a Post-war Village in Jaffna - Baskaran, N. (5 th International Research Conference of Uva Wellassa University, IRCUWU2021, 2021)
Many factors have contributed to the recent changes in families in Sri Lankan society and most of the factors are interlinked with the war. Socio-economic challenges faced by families due to resettlement became an essential topic in the post-war Jaffna due to many reasons. Therefore, the objective of the study is to identify the determined social-economic challenges faced by families after 30 years of resettlement, considering a case study of Myliddy North (J/246) village in Valikamam Jaffna. As a research method, qualitative and quantitative data techniques were used. The investigation is bifocal: one is at the community level and the other is household level. At the community level, primary data collection methods were meetings and interviews with key resource persons. At the household level with purposive and convenient sampling techniques, a total sample of 74 families were questioned through three-date collection tools namely, questionnaire surveys, in-depth interviews, and focus group discussion. As for the findings of the study through qualitative and quantitative analysis, it has been identified that the significant social and economic challenges faced by NRFs. One of the significant challenges that the people in the village face is the inability to obtain the use of land and the issues of landlessness (landless disabilities, landless women-headed family). Due to the military occupation, large scale of cultivated lands was destroyed, neglected, and abandoned by the owners which have created a lack of income with a new environment. Further, housing issues and homelessness tremendous, loss of community life, lack of leisure and other socio-cultural activities, and less safety and high-security zone issues disrupt the social life of the NRFs. The NRFs issues have become a central part of the development and social work discourses in the post-war villages in Jaffna. This study helps in identifying the kind of approaches and policies that need to formulated to address NRFs challenges and grievances.
Keywords: Post-war; Resettlement; Family structure; Socio-economic challenges